2011
DOI: 10.1007/s10597-011-9396-7
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the High Proportion of Involuntary Psychiatric Hospital Admissions in South Korea

Abstract: The 2007 WHO-AIMS report on the mental health system of South Korea documented progress towards a national mental health plan, protection of human rights, and growth of community based services. Yet concern was expressed that the high proportion of involuntary to total psychiatric hospitalizations (92%) may indicate an excessively coercive system. Involuntary hospitalization in Korea rose from 117 to 132 (per 100,000) between 2000 and 2006. In 2000, the median rate in the European Union (EU) was 74 per 100,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…This could lead to a lower percentage of involuntary admission in this study. However, in South Korea culturally mandated family referrals can override the patients’ wishes to initiate compulsory admissions, which may account for its high percentage of involuntary admission [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could lead to a lower percentage of involuntary admission in this study. However, in South Korea culturally mandated family referrals can override the patients’ wishes to initiate compulsory admissions, which may account for its high percentage of involuntary admission [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, the proportion of involuntary to total psychiatric hospitalizations, termed the involuntary admission quota, ranged from 3.2% to 26.4%, whereas the involuntary admission rate ranged from 6 to 218 with a median of 74 per 100,000 inhabitants across the EU [ 1 , 7 , 8 ]. However, only one study has been reported from the Asian country in South Korea where a high involuntary admission quota of 92% was noted in 2007 [ 9 ]. There remains a lack of studies about involuntary admissions in non-Western developed countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has created concern regarding forcible admission; however, it is suggested that these numbers must be viewed through a cultural lens. Bola, Park, and Kim (2011) indicate that these numbers can be attributed to the fact that stigma prevents individuals from voluntarily accessing treatment; also, these services may not be adequately supported financially for individuals.…”
Section: Social/cultural Stigmatization Of Mental Illnessmentioning
confidence: 99%
“…[5] Methods in implementing psychiatric commitment include consideration of individual's autonomy, and decision-making powers or referrals which may follow mandates that place the power to decide to non-medical authorities such as judges, courts, government officials, or social workers as well as family or significant others and decisions of the mental health professionals according to legal provisions. [6] Bola and col-leagues' study [7] in South Korea revealed that more than half (66%-77%) of involuntary admissions were referred primarily by the family while Rotvold and Wynn [8] accounted 25% in their study. Family involvement in the involuntary admission of the patient may pose long-term consequences in terms of relationship with the patient.…”
Section: Introductionmentioning
confidence: 98%